2020
DOI: 10.48550/arxiv.2003.00960
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tune modulation effects in the High Luminosity Large Hadron Collider

Sofia Kostoglou,
Hannes Bartosik,
Yannis Papaphilippou
et al.

Abstract: Several transverse noise sources, such as power supply ripples, can potentially act as an important limiting mechanism for the luminosity production of the Large Hadron Collider (LHC) and its future High-Luminosity upgrade (HL-LHC). In the presence of non-linearities, depending on the spectral components of the power supply noise and the nature of the source, such a mechanism can increase the diffusion of the particles in the distribution through the excitation of sideband resonances in the vicinity of the res… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…First, one must observe that the frequencies of the lines are not affected by the tune change. This fact proves that the harmonics are the result of a dipolar field error rather than a tune modulation [44]. Second, a comparison prior and after the trim leads to the conclusion that the amplitude of the lines in the vicinity of the betatron tune is strongly enhanced.…”
Section: Observations During Changes In the Beam And Machine Configur...mentioning
confidence: 73%
See 2 more Smart Citations
“…First, one must observe that the frequencies of the lines are not affected by the tune change. This fact proves that the harmonics are the result of a dipolar field error rather than a tune modulation [44]. Second, a comparison prior and after the trim leads to the conclusion that the amplitude of the lines in the vicinity of the betatron tune is strongly enhanced.…”
Section: Observations During Changes In the Beam And Machine Configur...mentioning
confidence: 73%
“…From the FMAs, it is observed that the dipolar noise results in an increase of the particles' diffusion, first, by enhancing the strength of some of the nominal resonances and second, through the excitation of additional resonances. In contrast to quadrupolar modulations [44], which lead to the excitation of sideband resonances, the location of the resonances in the presence of a modulated dipolar field error is equal to the frequency of the excitation. As the noise is injected in the horizontal plane, they appear as vertical lines in fixed positions for the low (black) and high (blue) frequency cluster.…”
Section: B Frequency Map Analysis With a Realistic Noise Spectrummentioning
confidence: 94%
See 1 more Smart Citation
“…The aim of the present paper is to determine whether the 50 Hz harmonics act as a limiting factor to the beam performance of the LHC, as well as its future upgrade, the High-Luminosity LHC (HL-LHC) [8], using single-particle tracking simulations with power supply ripple in the form of dipolar excitations. The impact of power supply ripple that results in a tune modulation is discussed in a previous paper [9]. First, the motion of a particle in the presence of a modulated dipolar field error is described using a linear formalism (Section II).…”
Section: Introductionmentioning
confidence: 99%